Giant Malignant Pheochromocytoma with Palpable Rib Metastases - Korgali, Esat (Hindawi Publishing Corporation, 2014)
Pheochromocytoma is a rare and usually benign neuroendocrine neoplasm. Only 10% of all these tumors are malignant and there are no definitive histological or cytological criteria of malignancy. Single malignancy criteria are the presence of advanced locoregional disease or metastases. We report a case, with a giant retroperitoneal tumor having multiple metastases including palpable rib metastases, who was diagnosed as a malignant pheochromocytoma. The patient was treated with surgery. The literature was reviewed to evaluate tumor features and current diagnostic and therapeutic approaches for patients with metastatic or potentially malignant pheochromocytoma.